Reproductive aging and elective fertility preservation - Rani Fritz; Sangita Jindal (Journal of Ovarian Research, 2018)
Abstract Reproductive aging is a natural process that occurs in all women, eventually leading to reproductive senescence and menopause. Over the past half century there has been a trend towards delayed motherhood. Postponing reproduction can increase the chance of a woman remaining involuntarily childless as well as an increase in pregnancy complications in those that do achieve pregnancy at advanced maternal age. Despite the well-documented decrease in fecundity that occurs as a woman ages, reproductive aged women frequently overestimate the age at which a significant decline in fertility occurs and overestimate the success of assisted reproductive technologies (ART) to circumvent infertility. Oocyte cryopreservation enables women to achieve genetically related offspring in the event that they desire to postpone their childbearing to an age after which a significant decline in fertility occurs or in circumstances in which their reproductive potential is compromised due to medical pathology. Available success rates and safety data following oocyte cryopreservation have been reassuring and is not considered experimental according to the American Society for Reproductive Medicine and the European Society for Human Reproduction and Embryology. This review article will focus on an evidence-based discussion relating to reproductive aging and oocyte cryopreservation.